2016
DOI: 10.1111/anu.12418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lipid sources on growth performance, lipid metabolism and antioxidant status of juvenile Russian sturgeonAcipenser gueldenstaedtii

Abstract: Six isonitrogenous and isoenergetic diets were used to test the influence of lipid source on growth performance, antioxidant status and lipid metabolism of juvenile Russian sturgeon, Acipenser gueldenstaedtii. Each diet was supplemented with 90 g kg À1 of lipid from each of six sources including fish oil (FO), beef tallow (BT), sunflower oil (SO), linseed oil (LO) and equal combinations of FO + SO + BT (FSB) or LO + SO + BT (LSB). After 56 days, fish fed LSB demonstrated highest weight gain, specific growth ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 78 publications
(131 reference statements)
1
9
0
2
Order By: Relevance
“…Overdose LC‐n‐3 HUFA could enhance oxidative stress and cell apoptosis by producing massive reactive oxygen species (ROS) (Ji, Li, & Liu, ; Todorčević et al, ). Li et al () reported that SOD and MDA in the Russian sturgeon juveniles fed fish oil diet were the highest in all groups when DHA+EPA level in fish fed oil diet was 15.0 g/kg diet. However, in the present study, uptrend CAT activities and stable MDA, SOD and T‐AOC levels with higher dietary DHA/EPA ratio in visceral mass of Siberian sturgeon also indicated homeostasis of lipid metabolism fed high DHA diet in larval stage.…”
Section: Discussionmentioning
confidence: 99%
“…Overdose LC‐n‐3 HUFA could enhance oxidative stress and cell apoptosis by producing massive reactive oxygen species (ROS) (Ji, Li, & Liu, ; Todorčević et al, ). Li et al () reported that SOD and MDA in the Russian sturgeon juveniles fed fish oil diet were the highest in all groups when DHA+EPA level in fish fed oil diet was 15.0 g/kg diet. However, in the present study, uptrend CAT activities and stable MDA, SOD and T‐AOC levels with higher dietary DHA/EPA ratio in visceral mass of Siberian sturgeon also indicated homeostasis of lipid metabolism fed high DHA diet in larval stage.…”
Section: Discussionmentioning
confidence: 99%
“…While the partial replacement of FO with VOs did not affect growth and feed utilization in some fish species [14,37], in other species the total replacement of dietary FO with VOs significantly impacted negatively on growth and fillet quality resulting in growth retardation, abdominal and hepatic fat deposition [22,29]. Studies on Catla catla fingerlings [38], Rohu carp Labeo rohita [39], sea bass Dicentrachus babrax [5], juvenile African catfish Clarias gariepinus [17], largemouth bass Micropterus salmoides [9], Russian sturgeon Acipenser gueldenstaedtii [8] and large yellow croaker [29] showed comparable growth performance of fish fed FO-supplemented diet to fish fed 100% VOs (SO, GO, PO, SFO, poultry fat) or blend of VOs.…”
Section: Growth Performance and Nutrient Utilizationmentioning
confidence: 99%
“…The success of any commercial aquaculture requires the provision of a balance mix of feed containing nutrients in the right proportion [5]. Of these nutrients, protein and lipid play essential roles as sources of protein, energy and essential fatty acid required for optimum fish growth [6][7][8]. These EFAs play vital roles in maintaining the structure and function of cell membranes [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, FO + VO diet resulted in the highest average weight, SGR, BWI, ADG and CF, whereas VO diet showed the lowest. In this regard, in the study ofLi et al (2017), juvenile Russian sturgeon (Acipenser gueldenstaedtii) fed equal combinations of linseed oil, sunflower oil and beef tallow resulted in highest WG and SGR among all groups (fish oil, linseed oil, sunflower oil, beef tallow, and equal combinations of fish oil, sunflower oil and beef tallow). Similarly,Gao and Chen (2004) reported that the highest growth performance results in juvenile Amur sturgeon (Acipenser schrenckii) were obtained with diets containing oil mixtures (fish oil: soya bean oil: lard = 1:1.2:0.8) or fish oil, while fish fed diets containing sunflower oil or lard performed to the contrary.…”
mentioning
confidence: 99%